Analisa Kebutuhan dan Perancangan Game Edukasi Pengenalan Makanan Hewan Untuk Siswa SD - Henri Septanto; Arum Kusuma Wardani; Nur Hayati; Harya Bima Dirgantara (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
Abstract:Needs Analysis and Design of Educational Games must be done before an educational game application program is used because Educational Games are currently not only an alternative in the learning process, but many have made it a part of the learning process. The system design is carried out using the GDLC model and the modeling language using UML (United Modeling Language). The implementation of this research is planned to produce a Learning Game application that is useful for elementary school students and also useful as a fun learning medium and also useful for elementary school teachers as a teaching aid. In accordance with the current situation and conditions coupled with the age of 1st grade elementary school children, where at that age children will prefer to learn while playing, then the analysis and design of this educational game is made with the hope that the resulting educational game will produce an educational game. games that support the learning process. Keywords: Analysis, Design. Game, Education